The relationship between paraoxonase, arylesterase, lipoprotein (a) and other lipid parameters in patients with coronary heart disease - Özdin, Mehmet; Gürsu, Mehmet Ferit (Sivas Cumhuriyet Üniversitesi, 2020)
Objective: Millions of people die every year in industrialized countries due to coronary heart disease (CHD) and rank first among the causes of mortality. It is vital to know the causes of CHD and to determine early diagnosis methods. Low antioxidant enzyme paraoxonase (PONl) activity in High Density Lipoprotein (HDL) structure, which prevents Low Density Lipoprotein (LDL) oxidation, is a risk factor for CHD. Method: For this purpose, serum PONl activities, ARE activities, Lp (a), apo A, apo B and other lipid parameters were investigated in 80 patients who were diagnosed with CHD who applied to the Cardiology Clinic of Fırat University Medical Faculty Hospital. CHD group; It consists of coronary heart patients who have undergone myocardial infarction to the cardiology outpatient clinic, or who have decided to by-pass operation as a result of coronary angiography, who use antiischemic drugs, have no diabetes, do not drink alcohol and smoke, do not have coronary heart disease in the family history, do not take lipid-lowering drugs. The control group consists of 40 healthy individuals without cardiovascular disease, diabetes or a disease affecting serum lipid level. Results: Cholesterol, triglyceride (TG), HDL, LDL, VLDL, serum PONl and ARE activities, Lp (a), apo A and apo B levels were found statistically significant in the CHD compared to the healthy control group (p <0.05). Serum PONl activity and ARE activity were lower in the patient groups compared to the healthy control group, and serum Lp (a) levels were higher (p <0.05). Conclusions: Serum PONI activity serum Lp (a) levels, which are accepted as important parameters in the diagnosis of CHD, were also found to be significant biochemical markers in our study.

Amaç: Koroner Kalp Hastalığı (KKH) nedeni ile endüstrileşmiş ülkelerde her yıl milyonlarca kişi ölmekte, mortalitenedenleri arasında ilk sırada yer almaktadır. KKH'nın nedenlerinin bilinmesi, erken tanı yöntemlerinin belirlenmesihayati önem taşımaktadır. High Density Lipoprotein (HDL) yapısında bulunan, Low Density Lipoprotein (LDL) oksidasyonunu önleyen ve antioksidan bir enzim olan paraoksonaz (PONl) aktivitesinin düşük olması KKH için bir riskfaktörüdür. KKH tanısı alan ve etiyolojik risk faktörleri taşıyan bireylerde serum PONl, arilesteraz (ARE) veLipoprotein(a) (Lp(a)) düzeyleri ile diğer lipit bileşenleri arasındaki ilişkinin araştırılması amaçlandı.Yöntem: Bu amaçla Fırat Üniversitesi Tıp Fakültesi Hastanesi Kardiyoloji kliniğine başvuran 80 KKH tanısıalan hastanın serum PONl aktiviteleri, ARE aktiviteleri, Lp(a), apo A, apo B ve diğer lipid parametreleriaraştırıldı. KKH’ları; kardiyoloji polikliniğine gelen miyokard infarktüsü geçirmiş veya koroner anjiografisonucunda by-pass operasyonuna karar verilmiş, antiiskemik ilaç kullanan, diabeti olmayan, alkol ve sigaraiçmeyen, aile hikayesinde koroner kalp hastalığı olmayan, lipit düşürücü ilaç almayan koroner kalphastalarından oluşmaktadır. Kontrol grubu kardiyovasküler hastalığı, diyabeti veya serum lipid düzeyinietkileyen bir hastalığı olmayan sağlıklı 40 bireyden oluşmaktadır.Bulgular: KKH'larında kolesterol, trigliserid (TG), HDL, LDL, VLDL, serum PONl ve ARE aktiviteleri, Lp(a), apo Ave apo B düzeyleri sağlıklı kontrol grubu ile karşılaştırıldığında istatistiksel olarak anlamlı bulundu (p<0.05). SerumPONl aktivitesi ve ARE aktivitesi hasta gruplarında sağlıklı kontrol grubuna oranla düşük, serum Lp(a) düzeyleri iseyüksek bulunmuştur (p<0.05).Sonuç: KKH tanısında önemli parametreler olarak kabul edilen serum PONI aktivitesi serum Lp(a) düzeyleriçalışmamızda da anlamlı biyokimyasal belirteçler olarak saptanmıştır.
Koroner kalp hastalarında paraoksonaz, arilesteraz, lipoprotein (a) ve diğer lipit parametreleri arasındaki ilişki
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi